Diurnal neurobiological alterations after exposure to clozapine in first-episode schizophrenia patients. (February 2016) - Sun, Hong-Qiang; Li, Su-Xia; Chen, Fang-Bin; Zhang, Yan; Li, Peng; Jin, Mei; Sun, Yan; Wang, Fan; Mi, Wei-Feng; Shi, Le; Yue, Jing-li; Yang, Fu-De; et al.
Highlights: System research for the first time on the changes of the circadian system, including clock genes, hormones and peptides, in the first—episode patients with schizophrenia. Compared with healthy controls, the first—episode schizophrenia patients showed disruptions in the diurnal rhythms of the expression of hPER1, hPER2, hPER3 and hNPAS2 and disruptions in the diurnal rhythms of the release of orexin. Several of these disruptions ( i.e., hPER1, hPER2, and hPER3 ) persisted 8 weeks after clozapine treatment, similar to the decreases in the 24 h levels of hPER3 and hNPAS2, accompanied by new changes in decreasing of hPER2 levels and increasing of insulin levels after clozapine treatment. Clozapine can restore both the disruptions in the diurnal rhythm and the levels of plasma cortisol in patients with schizophrenia. Abstract: Background: Irregular circadian rhythm and some of its most characteristic symptoms are frequently observed in patients with schizophrenia. However, changes in the expression of clock genes or neuropeptides that are related to the regulation of circadian rhythm may influence the susceptibility to recurrence after antipsychotic treatment in schizophrenia, but this possibility has not been investigated. Methods: Blood samples were collected from 15 healthy male controls and 13 male schizophrenia patients at 4 h intervals for 24 h before and after treatment with clozapine for 8 weeks. The outcome measures included the relative expression of clock gene mRNA PERIOD1 (PER1), PERIOD2 (PER2), PERIOD3 (PER3) and the levels of plasma cortisol, orexin, and insulin. Results: Compared with healthy controls, schizophrenia patients presented disruptions in diurnal rhythms of the expression of PER1, PER3, and NPAS2 and the release of orexin, accompanied by a delayed phase in the expression of PER2, decreases in PER3 and NPAS2 expression, and an increase in cortisol levels at baseline. Several of these disruptions ( i.e., in PER1 and PER3 expression) persisted after 8 weeks of clozapine treatment, similar to the decreases in the 24-h expression of PER3 and NPAS2 . Clozapine treatment for 8 weeks significantly decreased the 24-h levels of PER2 and increased the 24-h levels of insulin. Conclusion: These persistent neurobiological changes that occur after 8 weeks of clozapine treatment may contribute to the vulnerability to recurrence and efficacy of long-term maintenance treatment in schizophrenia.